2012
DOI: 10.1073/pnas.1119075109
|View full text |Cite
|
Sign up to set email alerts
|

Autoinhibition of Mint1 adaptor protein regulates amyloid precursor protein binding and processing

Abstract: Mint adaptor proteins bind to the amyloid precursor protein (APP) and regulate APP processing associated with Alzheimer's disease; however, the molecular mechanisms underlying Mint regulation in APP binding and processing remain unclear. Biochemical, biophysical, and cellular experiments now show that the Mint1 phosphotyrosine binding (PTB) domain that binds to APP is intramolecularly inhibited by the adjacent C-terminal linker region. The crystal structure of a C-terminally extended Mint1 PTB fragment reveals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…However, it is now clearly recognized that they play a dynamic role in finely tuning cellular information and responses (29,30). Mint1 and Mint2 play more sophisticated roles in achieving functional regulation through autoinhibitory mechanisms (31,32). We have shown previously that Mint1 undergoes a conformational switch between a "closed" state that does not bind APP and an "open" state involved in APP binding and that this switch plays a central role in regulating A␤ production (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is now clearly recognized that they play a dynamic role in finely tuning cellular information and responses (29,30). Mint1 and Mint2 play more sophisticated roles in achieving functional regulation through autoinhibitory mechanisms (31,32). We have shown previously that Mint1 undergoes a conformational switch between a "closed" state that does not bind APP and an "open" state involved in APP binding and that this switch plays a central role in regulating A␤ production (31).…”
Section: Discussionmentioning
confidence: 99%
“…Mint1 and Mint2 play more sophisticated roles in achieving functional regulation through autoinhibitory mechanisms (31,32). We have shown previously that Mint1 undergoes a conformational switch between a "closed" state that does not bind APP and an "open" state involved in APP binding and that this switch plays a central role in regulating A␤ production (31). In addition, previous NMR studies observed intramolecular contacts between the Mint1 C-terminal tail and the PDZ1 domain, which blocks it ability to bind exogenous targets such as PS1 (33).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have already studied the regulation of the Mint adaptor proteins and the impact on APP processing. It has been shown that Mint1 activity is controlled by autoinhibitory mechanisms [56]. In the autoinhibited state the C-terminus of Mint1 binds to the PTB domain and so undergoes a conformational change, which leads to the loss of its APP binding affinity.…”
Section: Discussionmentioning
confidence: 99%
“…For lentivirus production, Mint2-WT, Mint2-Y3E or Mint2-Y3F was inserted into the pLitmusIRES shuttle vector with a 5′ IRES and subsequently inserted into pFUW-NLS-EGFP- cre to generate pFUW-EGFP- cre -IRES-Mint2-WT, -Mint2-Y3E and -Mint2-Y3F plasmids. To generate GST-Mint2 peptides for in vitro phosphorylation analysis, PCR was used to amplify the rat Mint2 N-terminal region (Mint2-N; residues 1–399), the Mint2 N-terminal region containing Y3F mutations (Mint2-N-Y3F; residues 1–399), the Mint2-PTB domain (residues 363–546; Matos et al, 2012), or the Mint2 C-terminal region (Mint2-C; residues 546–750) which were then inserted into pGEX-KG. APPΔCT15 (residues 1–680) was amplified by PCR using human APP695 as a template and inserted into the pCMV5 mammalian expression vector.…”
Section: Methodsmentioning
confidence: 99%